Optimizing Bokashi Fertilizer Dosage on the Growth of Corn Plants (Zea mays L) Local Varieties of North Sumatra That Have Been Irradiated with Gamma Rays - Annisyah Sepyanti; Novilda Elizabeth Mustamu; Badrul Ainy Dalimuthe; Yudi Triyanto (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Corn (Zea mays L.) is a primary agricultural commodity in Indonesia, alongside rice and soybeans. This study aims to evaluate the growth of local corn plants in North Sumatra after applying various doses of bokashi fertilizer. The research was conducted in Perbaungan Village, Bilah Hulu District, Labuhanbatu Regency, North Sumatra, from December 2024 to February 2025. The study employed a Completely Randomized Design (CRD) with a one-factor experiment, focusing on applying bokashi fertilizer to corn plants. Five treatments were tested: Control (no application), 80 grams per polybag (4 x 20 grams every 2 weeks), 120 grams per polybag (4 x 30 grams every 2 weeks), 180 grams per polybag (4 x 40 grams every 2 weeks), and 200 grams per polybag (4 x 50 grams every 2 weeks). The parameters observed included plant height, number of leaves, and stem diameter. Data analysis was performed using the Tukey Test (BNJ) at a significance level of 5%. The results indicated that the application of bokashi fertilizer significantly influenced the growth of local corn in North Sumatra, with the most favorable outcomes observed at 8 weeks after planting (WAP). The highest plant height recorded was 141.65 cm (P4), the number of leaves was 11.50 strands (P3), and the stem diameter measured 2.73 cm (P4).